Formation of Special Anti-Corruption Detachments and its relation to the potential for dualism in the eradication of corruption in Indonesia - Syariefudin, Iqbal Syariefudin (Lex Scientia Law Review, 2018)
The Corruption Eradication Commission is a state institution that in carrying out its duties and authority is independent and free from the influence of any power. other law enforcement agencies such as the police, the prosecutor's office is still not optimal in efforts to eradicate corruption in Indonesia, the Corruption Eradication Commission is arguably a fresh air in efforts to eradicate corruption, it is expected that the Corruption Eradication Commission becomes an independent institution in eradicating corruption, there is no intervention from anywhere , so that in its implementation it is indiscriminate, professional, intensive, and realize the expectations of the community to suppress the smallest possible criminal acts of corruption.